Sexual Harassment of Workers in The Workplace - Mistirah, Khoiriah; Wijayanti, Asri (Faculty of Law, University of Muhammadiyaha Surabaya, 2022)
Sexual harassment in the workplace that is not taken seriously causes unsolved issues of widespread sexual harassment and unsafe workplace for people.This legal research uses a statutory approach and a conceptual approach. The legal questions asked are: 1) What is the form of legal protection for workers who experience sexual harrasment in the work place? 2) what legal remidies can be taken by workers who experience sexual harassment in the workplace?Â The results of the study show that the protections given to sexual harassment victims are; 1) being able to file for layoffs if the sexual harassment is carried out by entrepreneurs, the termination of layoffs for workers who are perpetrators of sexual harassment, and the threat of criminal sanctions against perpetrators of sexual harassment. Workers who are victims of sexual harassment who file for layoffs are entitled to one-time severance pay, one-time work award and compensation. 2) Legal remedies that can be taken by victims of sexual harassment in the workplace are civil law action through non-litigation or litigation and can also take criminal legal action by submitting a complaint to the police.